Markerless motion analysis in sports and exercise - Bini, R. R.; Colyer, S.; Moura, F. A.; Santiago, P.; Vanicek, N. (Journal of Sports Sciences, 2026)
For over a century, motion analysis has been a fundamental tool for scientists wishing to analyse and interpret movement patterns of humans and animals. A couple of key early examples include the work done in the 1880s by Étienne-Jules Marey, who recorded sequences of human gait, and the "The Horse in Motion" experiment from Eadweard Muybridge in 1878. These pioneering efforts set the scene for our ongoing commitment for developments in our understanding of how we move, and the implications for enhanced human performance, injury prevention and complex pathological movement patterns. Since the early 1970s, movement analysis involved using one or more cameras to track landmarks on the body to describe how segments were contributing to a person`s movement. This method involved manual pre-identification and marking of these landmarks on the skin using active or passive markersthat could be visualised by cameras. The improvement in computer technology streamlined the tracking, enabling scientists to automatically determine the location of these markers in space at various phases of movement.